2019
DOI: 10.1007/978-3-030-29387-1_39
|View full text |Cite
|
Sign up to set email alerts
|

Is Bigger Better? A Fitts’ Law Study on the Impact of Display Size on Touch Performance

Abstract: Touch-sensitive surfaces are already a standard form of interaction. These surfaces come in many different sizes like tablets or touch walls. However, there is little research to characterize the impact of surface size on touch performance. We conducted a Fitts' Law study of three display sizes (13.5" tablet, 28" monitor, 69.5" large monitor), comparing various performance measures. We found that the smallest size (13.5") is problematic both objectively (high error rate) and subjectively (imprecise, difficult-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Thus, our results for throughput values for mid-air tapping with fog are 32% higher than the 1.75 bps reported previously for pure mid-air tapping [15]. Furthermore, the results are comparable with the values of 2.10-2.25 bps for mid-air gesture selection with large conventional displays, where selection confirmation was executed by voice or button press [18,19] but lower than the values of 4-6 bps for large touchscreen interaction [34,35]. Regarding dwell-based selection with fog, its throughput is also comparable to the values of 1.7-1.9 bps previously reported [15,21].…”
Section: Discussionsupporting
confidence: 56%
“…Thus, our results for throughput values for mid-air tapping with fog are 32% higher than the 1.75 bps reported previously for pure mid-air tapping [15]. Furthermore, the results are comparable with the values of 2.10-2.25 bps for mid-air gesture selection with large conventional displays, where selection confirmation was executed by voice or button press [18,19] but lower than the values of 4-6 bps for large touchscreen interaction [34,35]. Regarding dwell-based selection with fog, its throughput is also comparable to the values of 1.7-1.9 bps previously reported [15,21].…”
Section: Discussionsupporting
confidence: 56%
“…Touch screens have previously been reported to be faster but less accurate than a mouse (Burno et al, 2015; Sambrooks & Wilkinson, 2013, Stevenson et al, 2004). When using vision to guide movement termination on a touch screen, the finger/hand may obscure site of the target (see Van Veldhuizen & Yang, 2021) and this may be a greater problem on smaller screens (List & Kipp, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the small-sized screen was divided into several rectangular areas for performance evaluation. List and Kipp (2019) compared the middle-sized and large-sized touchscreen devices and found that the middle-sized devices allow for greater interaction speed but a high error rate.…”
Section: Introductionmentioning
confidence: 99%